Specialized software modelling comlex "Physiolresp" - Grigiryan, R.D.; Lissov, P.N.; Aksionova, T.V.; Moroz, A.G. (PROBLEMS IN PROGRAMMING, 2026)
Concepts, mathematical models and software for theoretical study of general rules determining human organism responses to alterations of environmental physical–chemical characteristics are proposed. The software modeling complex (SMC) includes 5 models: мechanism of reactive cell adaptation to induced energy deficit (IED); мechanism of main physiological systems integration for IED minimization in a group of cells; мechanisms of physical changes and physiological responses of cardiovascular system and kidney under atmosphere pressure changes; мechanism of thermoregulatory responses to IED; мodel of external environmental characteristics. Technology of SMC usage is illustrated in test examples.Problems in programming 2009; 2: 67-82